56.3k views
4 votes
1) Given f(x) = x+5 and g(x) = 11x - 5 , what is f(x) + g(x)

A) 2x
B) 11x
C) 12x
D) 55x - 25

2) Given f(x) = x + 11 and g(x)=3x , what is f(5)+g(-2)

A)16
B) 10
C) 22
D) -6

3) Using f(x)=4x+2 and g(x)=6x , what is g(x)-f(x)?

A) - 6x
B) 2x - 2
C) -2x + 2
D) 4x + 6

4) Using f(x)=3x-3 and g(x)=2x , what is f(4) - g(2)?

A) 5
B) -5
C) 10
D) -10

User Courtnie
by
5.2k points

2 Answers

4 votes

Answer:

1:C 2:B 3:C 4:A

Explanation:

1.) x + 11x = 12x

5 - 5

12x

____________

2.) f(5) = 5 + 11

g(-2) = 3(-2)

16 - 6 = 10

___________

3.) 4x - 6x + 2 = -2x + 2

_________________

4.) f(4) = 3(4) - 3

12 - 3 =9

g(2) = 2(2) = 4

9 - 4 = 5

User NonowPoney
by
5.2k points
5 votes

Answer:

1)c 2)b 3)c 4)a

Explanation:

1)x+5+11x-5

12x

2)5+11-6

10

3)4x+2-6x

-2x+2

4)12-3-4

5

User Aynber
by
5.3k points